2018
DOI: 10.1245/s10434-018-6445-2
|View full text |Cite
|
Sign up to set email alerts
|

Progression Patterns in the Remnant Pancreas after Resection of Non-Invasive or Micro-Invasive Intraductal Papillary Mucinous Neoplasms (IPMN)

Abstract: In this study, 22% of patients had disease progression following resection of noninvasive or microinvasive IPMN; 16% of these progressions represented invasive disease. These patients represent a high-risk group and should undergo long-term radiographic surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 23 publications
2
27
1
Order By: Relevance
“…38,39 Conversely, accumulating evidence suggests that patients with branch-duct IPMNs may remain at high risk of developing pancreatic carcinoma after 5-year surveillance. 9,[40][41][42] Few large studies have examined pancreatic carcinogenesis associated with branch-duct IPMNs specifically among patients with no considerable change during 5-year surveillance. In a study at a US referral center, high-grade dysplasia and invasive carcinoma were observed in 20 (5.5%) and 16 (4.4%) patients, respectively, of 363 patients included at the time of 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Conversely, accumulating evidence suggests that patients with branch-duct IPMNs may remain at high risk of developing pancreatic carcinoma after 5-year surveillance. 9,[40][41][42] Few large studies have examined pancreatic carcinogenesis associated with branch-duct IPMNs specifically among patients with no considerable change during 5-year surveillance. In a study at a US referral center, high-grade dysplasia and invasive carcinoma were observed in 20 (5.5%) and 16 (4.4%) patients, respectively, of 363 patients included at the time of 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intrapancreatic recurrence during follow-up, the possibility of extrapancreatic recurrence should also be considered. Extrapancreatic recurrence from non-invasive IPMN is thought to be rare [10,11,14,[19][20][21][22], although metastatic recurrence of invasive IPMN to extrapancreatic organs was reported at a high rate of 45-57% [20,23]. Thus, a protocol for long-term postoperative surveillance is required so as not to miss any recurrence after IPMN resection because the risk of intra-and extrapancreatic recurrence increases year by year.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the ndings of most previous studies on IPMN. [20][21][22] Kerlakian et al, demonstrated that jaundice was more often seen in patients with uncinate or head cysts (14.9% vs. 1.9%, p < 0.01) and that incidentally discovered or asymptomatic IPMN were more likely in patients with tumors located in the neck, body, or tail of the pancreas (53.3% vs. 31.0%, p < 0.01). 23 Furthermore, the median time from diagnosis to surgery was shorter.…”
Section: Discussionmentioning
confidence: 99%